PENINGKATAN HASIL DAN AKTIVITAS BELAJAR SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH (ICM) DAN MEDIA PETA KONSEP - Ulia Rita Sila, Vinsensia (Gema Wiralodra, 2019)
The research aims (1) to know the improvement of Biology learning outcomes, material learning activities of living creatures organizational systems with cooperative learning model Index Card Match (ICM) type, (2) to find out student responses to the cooperative learning model Index Card Match (ICM) in learning material life organism system organization. The study was conducted at Polen SMPS, Puna Village, Polen Subdistrict, TTS Regency in June to August 2018, with 21 students as the subject. The results showed that the pre-research test results with a percentage of 61.90% classical completeness, while 100% continued research. The average score of pre-research student activity is 2, 99 with a fairly good category, while the average score of student activity in the 3.50 study is in the good category. Respondents gave a positive response by choosing a score of 3 in my aspect I like to study the material of living creature organization system material and I understand the material of living creature organization system using concept map media and look for pairs of cards with a percentage of 76% in pre-research, while in the research respondents gave a positive response by choosing a score of 4 in the aspect of the sentence in the media concept map can I easily understand and the sentence on the question card can easily be understood by a percentage of 100%.            Keywords: Mind Mapping, Index Card Match   (ICM), Learning Achievement, Learning Activity, Student Response.